Evaluation of isatuximab in patients with soft-tissue plasmacytomas: An analysis from ICARIA-MM and IKEMA. (November 2022) - Beksac, Meral; Spicka, Ivan; Hajek, Roman; Bringhen, Sara; Jelínek, Tomas; Martin, Thomas; Mikala, Gabor; Moreau, Philippe; Symeonidis, Argiris; Rawlings, Andreea M.; van de Velde, Helgi; Richardson, Paul G.
Abstract: The Phase 3 ICARIA-MM (NCT02990338) and IKEMA (NCT03275285) studies demonstrated that isatuximab (Isa) plus pomalidomide (P) and dexamethasone (d; Isa-Pd) or carfilzomib (K) and d (Isa-Kd) improved progression-free survival (PFS) versus Pd or Kd in patients with relapsed and/or refractory multiple myeloma. In this post hoc analysis of patients with soft-tissue plasmacytomas, we evaluated Isa-Pd/Isa-Kd efficacy using central radiology and central laboratory assessments. Given the low incidence of soft-tissue plasmacytomas (7.8 %, ICARIA-MM; 6.3 %, IKEMA), efficacy data were pooled across the two studies. PFS (HR, 0.47; 95 % CI, 0.21–1.08), overall response rate (50.0 % vs 17.7 %), and very good partial response or better rate (26.9 % vs 11.8 %) were improved with Isa-Pd/Isa-Kd versus Pd/Kd, with consistent improvements within individual studies. Patients with soft-tissue plasmacytomas who received Isa-Pd/Isa-Kd had similar median PFS compared with those without soft-tissue plasmacytomas and received Pd/Kd. Safety is reported individually per study. Longer median treatment duration and more Grade ≥ 3 treatment-emergent adverse events occurred in the Isa versus control arms in ICARIA-MM (36.9 vs 8.4 weeks; 85.7 % vs 70.0 %) and IKEMA (41.9 vs 29.9 weeks; 100.0 % vs 57.1 %); however, Isa did not increase the percentage of patients with fatal events or drug discontinuation. Isa-Pd or Isa-Kd is a potential new treatment option and partially overcomes the poor prognosis associated with soft-tissue plasmacytomas in relapsed and/or refractory multiple myeloma. Graphical Abstract: ga1 Highlights: In Phase 3 ICARIA-MM and IKEMA, Isa plus Pd or Kd improved PFS in RRMM patients. Prospective data on outcomes for MM patients with soft-tissue plasmacytomas are rare. This post hoc analysis assessed Isa-Pd/Isa-Kd vs Pd/Kd in this unmet need subgroup. Isa-Pd/Isa-Kd improved PFS and partially overcame poor prognosis in this subgroup. Isa-Pd and Isa-Kd had a manageable safety profile in this high-risk subgroup.